In silico evaluation of the antiinflammatory potential of indolic alkaloids present in the seeds of Couroupita guianensis (Research, Society and Development, 2021)
Objective: To carry out a molecular modeling study to assess the anti-inflammatory potential of secondary metabolites from seeds of the botanical species Couroupita guianensis. Methodology: A quantitative, descriptive study with an experimental character was carried out. In order to confirm the predictive capacity of the methodology during molecular coupling, a redocking was performed. Nimesulide was used, due to its already elucidated ability to interact with COX-1 amino acids, as a comparison for the interactions between the alkaloids chosen for coupling. The alkaloids structures were obtained using the PubChem platform, and their design was carried out using the ChemDraw program. The alkaloids were also subjected to computational tests to assess their molecular properties. Results: The potential of anti-inflammatory activity present in the studied alkaloids was verified, in addition to the identification of the interactions of the compounds with amino acids. Conclusion: It can be concluded that the alkaloids identified have promising anti-inflammatory activity, which is due to their ability to interact with the active site of COX-1.